Different Personality Nuances Caused By Translation Differences (Semantic Analysis of Fictional Characters Personality Differences Caused By Japanese and English Dialogue Translation in Genshin Impact) - Hardianto Rahardjo (Universitas WIdyatama, 2021)
Genshin Impact is a video game developed by miHoYo, a Shanghai based video game developer and animation studio. Launched globally as an online Action Role Playing Game at September 28th 2020, Genshin Impact, or just Genshin in Japanese, came with voiceover dialogues in its cinematic dubbed in 4 different language, which is Chinese, English, Korean and Japanese. Genshin‘s user interface and dialogue subtitles also came translated into many other languages including simplified Chinese, traditional Chinese, English, French, German, Indonesian, Japanese, Korean, Portuguese, Russian, Spanish, Thai and Vietnamese. Translating the texts and dialogues into multiple languages, albeit still carry the main idea of the story and game concept, occasionally causing different nuances and meanings among different language. For example, the personality and characteristics of the game‘s fictional characters sometimes are being depicted differently in each language. This article is written in with the aim of presenting some examples and analysis concerning those differences in each language translation.